The corrosion behavior of cold drawn pure magnesium mini-tube for biomedical application. (16th November 2018) - Li, Cheng-Jie; Sun, Hong-Fei; Cheng, Shuang; Tan, Hong-Mei; He, Tian-Hong; Fang, Wen-Bin
Abstract: In this study, a combined method based on cold extrusion and cold drawing was used to fabricate pure Mg mini-tubes. Their mechanical properties and corrosion behavior in simulated body fluid were systematically investigated. The results demonstrated the as-drawn pure Mg tube exhibited superior strengths with yield strength and ultimate tensile strength of 146.9 ± 5.3 MPa and 187.4 ± 7.4 MPa, respectively. Moreover, the as-drawn pure Mg tube also revealed relatively good corrosion resistance. After soaking in SBF for 144 h, the average corrosion rate of the pure Mg tube is 0.36 ± 0.03 mm y −1 . The refined microstructure and strong basal texture induced by severe plastic deformation account for the improvement of corrosion resistance.